2023
DOI: 10.1097/pec.0000000000002892
|View full text |Cite
|
Sign up to set email alerts
|

Frontline Medical Professionals' Ability to Recognize and Respond to Suspected Youth Sex Trafficking

Abstract: Objectives: Many youth sex trafficking victims visit health care facilities while being trafficked. Little is known regarding whether frontline medical professionals recognize risk factors or are aware of effective interviewing approaches to identify and intervene for youth victims. The aim of the present study was to assess frontline medical professionals' knowledge of youth sex trafficking, adolescent development, and forensically informed interviewing to provide guidance for professional training. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 25 publications
(46 reference statements)
1
7
0
Order By: Relevance
“…Common stereotypes about victims, as well, may run counter to actual victims' presentations, reducing professionals' knowledge of trafficking but also their knowledge of which adolescents might be presenting with cues. Surveys of other professionals have also highlighted tendencies toward endorsing stereotypes about trafficking and difficulties identifying actual characteristics (Winks et al, 2023), a pattern we also observed here.…”
Section: School Professionals' Knowledge and Trainingsupporting
confidence: 81%
See 3 more Smart Citations
“…Common stereotypes about victims, as well, may run counter to actual victims' presentations, reducing professionals' knowledge of trafficking but also their knowledge of which adolescents might be presenting with cues. Surveys of other professionals have also highlighted tendencies toward endorsing stereotypes about trafficking and difficulties identifying actual characteristics (Winks et al, 2023), a pattern we also observed here.…”
Section: School Professionals' Knowledge and Trainingsupporting
confidence: 81%
“…Each vignette contained six cues to trafficking. Cues were based on details in prior trafficking or pandering criminal cases involving youth victims prosecuted in California (Quas et al, 2022), and the vignettes are highly similar to those used in prior studies of healthcare professionals' ability to recognize trafficking of minors (Winks et al, 2023), but were adapted for school settings. The cues in the first vignette were more ambiguous than the cues in the second, so the order was standardized.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This hostility may reduce the officers’ provision of support during an interview and increase their use of interrogative practices to obtain information (Dianiska et al, 2023), both of which are associated with decreases in disclosure completeness in victims and suspects (Meissner et al, 2012; Saywitz et al, 2019). In addition, law enforcement and other professionals may not believe claims made by youth who appear complicit with the sexual activities, who behave in a hostile manner, or who have a history of delinquency (Luna et al, 2023; Winks et al, 2023). Finally, introducing details in court about victims’ delinquency could increase perceptions that they are responsible for their experiences, just as perceptions of adolescent victims’ responsibility for sexual assault increase when they are described as having engaged in age-inappropriate behavior (e.g., having been in a bar) (Rogers et al, 2016).…”
Section: Introductionmentioning
confidence: 99%